Uniaxial compressive strength of Antarctic Peninsula rocks: Schmidt hammer rebound test - Goh, Thian Lai; Nur Amanina Mazlan,; Mohd Shahrul Mohd Nadzir,; Abdul Ghani Rafek,; Ailie Sofyiana Serasa,; Azimah Hussin,; Lee, Khai Ern; Foong, Swee Yeok (Penerbit Universiti Kebangsaan Malaysia, 2017)
The uniaxial compressive strength test is a destructive and time consuming test. A number of non-destructive methods using portable testing equipment are more applicable and easier to conduct. This paper presents the results of a systematic approach to determine the uniaxial compressive strength of rock material using the Schmidt hammer rebound test. A total of five distinct locations (Graham Coast, Davis Coast, Nanson Island, Danco Coast and Trinity Island) were tested using the Schmidt rebound hammer test. Peninsula Antarctic located at northwest of Antarctic region comprising of igneous and metamorphic rocks. Statistical analysis of the results at 95% confidence level showed the Schmidt rebound value of the Graham Coast ranges from 40±1.7 to 41±1.3 with standard deviation of 8.2 to 6.4. The rebound value for Davis Coast was 39±1.6 with standard deviation of 7.7. Rocks from Nanson Island and Danco Coast have the Schmidt rebound value of 54±1.7 with standard deviation of 8.0 and 36±1.3 with standard deviation of 6.2, respectively. The Schmidt rebound value of rocks at Trinity Island ranges from 29±1.4 to 32±1.7 with standard deviation of 6.8 to 8.1. Thus, the respective uniaxial compressive strengths of rock materials from Graham Coast, Davis Coast, Danco Coast, Nanson Island and Trinity Island were 73-108, 50, 59, 164 and 45-59 MPa. The respective ISRM strength classification of rock materials of Graham Coast, Davis Coast, Danco Coast, Nanson Island and Trinity Island were strong (R4) to very strong rock (R5), medium strong rock (R3), strong rock (R4), very strong rock (R5) and medium strong (R3) to strong rock (R4). The results showed a mean of quantification of rock material strength based on the Schmidt Hammer rebound test in Antarctic Peninsula.